Beef sauce assembly line and online sampling device - HAN YUBAO; HE DEJIN; MA ZHIGANG (2023)
The invention provides a beef seasoning sauce assembly line and an online sampling device, and relates to the technical field of beef seasoning sauce manufacturing. The material screening unit is used for screening beef particles and ingredients, mixing the beef particles and the ingredients, and discharging materials upwards through a spiral feeding pipe; the marinating and boiling unit comprises a material boiling machine, a sorting box, a cold water box and a marinating material box; respectively cooking the beef granules and the ingredients, sorting, cooling with cold water and marinating; the curing unit comprises a fixing frame, a frying pan, a rotating mechanism and a discharging box, one end of the frying pan is hinged to the fixing frame, and the rotating mechanism is suitable for rotating the frying pan; the unloading box is mounted on one side of the frying pan and is provided with a discharge pump I; the filling unit is used for filling beef sauce into the tank body; the cap screwing unit comprise